Nano-Modification of Epoxy Coatings on Concrete Using Graphene Derivatives - Nagaraj, Shivani (My University, 2022)
One of the major reason for the degradation of concrete structure is due to its permeability because of which water and other aggressive ions like chloride, sulphate and carbonates can enter the substrate causing damage to the concrete. Surface treatment has gained wide acceptance due to effective permeability resistance in concrete and also due to the fact that it can be applied to new as well as existing structures. Epoxy resin coating modified with two graphene derivatives i.e. graphene oxide (GO) and reduced Graphene Oxide (rGO) has been explored after coating concrete surfaces. Varying percentages including 0.1%, 0.2% and 0.3% of GO and rGO was studied to optimise the dosage of epoxy modified coating. Later in the same study the two existing coats has been modified with the help of 0.1% of Carbon Nano Tubes (CNT) to improve the dispersion property of nano- fillers. Water permeability property and chloride permeability of concrete were majorly studied to prevent untimely degradation of the concrete structure. Contact angle was used to understand the extent of water repelling property of modified nano filler coating. A comparison analysis is done for the same. Various tests revealed that nano- fillers at optimum levels of addition showed reduced permeability property and enhanced hydrophobicity. Contact angle revealed that 0.2% GO saw a maximum enhancement of 100 degrees hence showing the best hydrophobicity. Water ingress properties were measured using water absorption, sorptivity, and water permeability tests and it saw a decrease of 46%, 66% and 75% respectively after inclusion of 0.2% GO in epoxy coating. The chloride ion permeation showed “very low permeability” class according to ASTM C1202. This enhancement in the property can be attributed to the hydrophobicity, tortuosity, and pore-filling capability of nano- fillers in epoxy coating. Addition of CNT helped enhance the dispersion of nano fillers but did not show much enhancement in hydrophobicity up to 0.3% as compared to GO and rGO modified epoxy coatings.
Keywords: Nano-materials; Graphene Derivatives; Coatings; Epoxy; Graphene Oxide; Reduced Graphene Oxide; Surface Protection